A novel SEPT12 mutation, T96I, is associated with sperm head and annulus defects - Chen, Kuan-Ru; Wang, Han-Yu; Kuo, Yung-Che; Lo, Yu-Chih; Kuo, Pao-Lin (Frontiers in Cell and Developmental Biology, 2025)
Infertility affects around 8%–12% of reproductive-aged couples and is a major health concern. Both genetic and environmental factors influence male infertility. SEPTIN12 is a crucial testis-specific gene essential for the final differentiation of male germ cells and is strongly linked to male infertility due to numerous detected mutations. The present study identified a novel SEPTIN12T96I mutation that causes male infertility. Immunofluorescence staining and transmission electron microscopy (TEM) analysis of T96I sperm revealed co-localization of SEPT12 and SEPT7 in the obliquely positioned annulus. In addition, the sperm carrying the T96I mutation demonstrated large nuclear vacuoles, irregular swelling, and decondensation of the acrosomal cap. The overexpression of SEPT12 T96I in NT2/D1 cells impaired the formation of SEPT7 filaments, emphasizing the significance of SEPT12 filaments for sperm morphology and function. Our results demonstrate the importance of SEPTIN12T96I in male infertility and offer valuable insights for future detection in infertile men.